High intermediate precision Sm isotope measurements in geological samples by MC-ICP-MS. Issue 3 (13th February 2023) - Bai, Jiang-Hao; Lin, Mang; Zhong, Song-Xiong; Deng, Yi-Nan; Zhang, Le; Luo, Kai; Wu, Hao; Ma, Jin-Long; Wei, Gang-Jian
Abstract : A protocol for high intermediate precision Sm isotope measurements. Abstract : The measurement of Sm isotopes in geological materials is challenging, thus limiting their extensive applications in geoscience and environmental science. Herein, we developed a technique for the high intermediate precision analysis of Sm isotopes via multi-collector-inductively coupled plasma-mass spectrometry (MC-ICP-MS). Interference impurities, particularly Nd, Eu, and Gd, were completely removed from Sm using a new two-column [AG50W-X12 (200–400 mesh) and TODGA (50–100 μm)] procedure, which quantitatively (99.4 ± 0.3%) extracted Sm. The complete purification of Sm allowed the development of a high intermediate precision calibration method combined with standard-sample bracketing and Eu internal normalization to correct the instrumental mass bias. A long-term intermediate precision better than 0.04‰ (2SD) for δ 152/149 Sm was obtained. This intermediate precision is significantly better than those of the existing MC-ICP-MS methods (0.15‰–0.30‰) and double spike-thermal ionization mass spectrometry methods (0.15‰–0.20‰), as confirmed by multiple purifications and measurements of 11 geological reference materials (GRMs) with different rock types ( e.g., basalt, andesite, granodiorite, granite, nepheline, syenite, manganese nodule, and marine sediment). In addition, we observed a detectable variation in δ 152/149 Sm (0.22‰) among these 11 GRMs, which could not be identified at the previous intermediate precision. This finding highlights that the high intermediate precision δ 152/149 Sm measurements in natural samples established herein have the potential to provide new constraints on diverse natural processes, ranging from planetary formation to chemical weathering and ocean circulation and create new opportunities for stable Sm isotope studies.